Thermodynamic limits of adsorption heat pumps: A facile method of comparing adsorption pairs. (September 2019) - Jiang, Yingchun; Bagheri, Morteza H.; Loibl, Rebecca T.; Schiffres, Scott N.
Graphical abstract: Highlights: Ideal adsorption isotherm behavior as a function of operating conditions. Theoretical heating performance limits for AHPs. Highly efficient adsorbents for AHPs exhibit step-like isotherms, such as MOF 801. Facile heating performance comparisons of AHPs using different adsorbents. Abstract: Adsorption heat pumps (AHPs) transform a small quantity of input thermal energy into a greater quantity of lower temperature thermal energy. This transformation enables more efficient usage of thermal energy, reducing primary energy consumption and greenhouse emissions. In this paper, the theoretical thermodynamic limits of the AHP cycle are explored by deriving the ideal adsorption isotherm behavior as a function of operating conditions. An idealized AHP using adsorbents with step-like isotherms is evaluated for space heating. The properties of this idealized adsorbent that govern heating performance are identified as the adsorption step-location and the heat of adsorption. In addition, this analysis is extended to AHPs using non-ideal adsorbents with more and less step-like isotherms (MOF 801 and Zeolite 13X). The maximum coefficient of performance is calculated to be 1.6 for MOF 801 with a regeneration temperature of 76 °C and 1.5 for Zeolite 13X with a regeneration temperature of 120 °C. As this illustrates, more step-like adsorbents enable lower regeneration temperatures, which are particularly useful if a low-grade renewable heat source is available (e.g., solar thermal). This study provides a thermodynamic framework for selecting highly efficient adsorbents for AHPs, and enables facile comparisons of the heating performance of AHPs using non-ideal adsorbents.